A RATIONAL EFFICIENCY DEFINITION FOR HEAT EXCHANGERS - González-Mora, Eduardo (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
Heat exchangers are fundamental devices in thermal systems, widely employed in industrial applications, power generation, and thermal conversion processes. Engineers commonly evaluate their performance using two principal methodologies: the log-mean temperature difference (LMTD) and the effectiveness ‒ NTU method. However, these metrics present limitations, such as dependence on outlet temperatures or circular efficiency definitions, which hinder rigorous assessment of thermal performance. This study proposes a new performance function for heat exchangers, based on the ratio of heat transferred to heat available and expressed using average stream temperatures. We demonstrate that this approach avoids the circularity inherent in conventional definitions and enables a more accurate characterization of thermal performance across different flow configurations. Our parametric and sensitivity analysis reveals that effectiveness (ε) is the dominant performance variable and that flow arrangement significantly influences heat transfer. Compared to previous methodologies, this new indicator provides a unified framework for evaluating and optimizing heat exchangers in practical applications. These findings establish a solid basis for enhancing heat exchanger design and efficiency within industrial systems.